The Rubber Export Performance to the United States: A Comparison Between Indonesia and Thailand - Baroh, Istis; Relawati, Rahayu; Shodiq, Wahid Muhammad; Ramli, Mona Fairuz (HABITAT, 2024)
This research is used to compare the rubber export performance between Indonesia and Thailand to the United States market. The performance’s aspects will be compared with the volume and export value in the period of 2012-2022, the strict competitiveness of the United States market, and the factors that impact the volume and export value of rubber in the United States market. Secondary data from 2013-2022 was collected from any sources. This method of analysis used descriptive quantitative, Revealed Comparative Advantage (RCA), and multiple linear regression. The result shows that the export performance in Indonesia suffered a drop in volume aspects; however, the export volume from Thailand to the United States experienced an increase. The RCA rubber in Indonesia has an average value of 77.75 (strong competitiveness to the United States market), while the rubber quality in Thailand is about 19.28. The factors of world prices and productivity influence the export value of rubber from Indonesia to the United States; however, inflation, the rate of exchange of the dollar, and the income per capita of the United States do not influence the export value of rubber from Indonesia. The world price factor, the rate of exchange of the United States dollar against the Thai Baht, and the income per capita of Thailand have a positive effect on rubber exports from Thailand to the United States. The policy implication is Indonesian government should pay attention to maintain rubber production sustainability to defense the competitiveness of the export.